A Teaching Essay on Residual Stresses and Eigenstrains. - Korsunsky, Alexander (Elsevier Science, 2017)
Residual stresses are an important subject in materials science and engineering that has implications across disciplines, from quantum dots to human teeth, from aeroengines to automotive surface finishing. Although a number of monographs exist, no resource is available in the form of a book to serve as a good basis for teaching the fundamentals. A Teaching Essay on Residual Stresses and Eigenstrains introduces eigenstrain methods as a powerful unified approach to residual stress modeling, measurement, and management. Starting with simple residual stress states, the key relationships are elucidated between deformation processes, inelastic strains (eigenstrains) these may introduce, and the resulting residual stress states. This book is written not only for the materials scientist, mechanical engineer, and student seeking to appreciate the origins of residual stress, but also for the more mature researcher and industrial engineer looking to improve their understanding of the eigenstrain approach to describing residual stress.